Examining Indonesian Government Policies in Tackling Deforestation: Balancing Economy and Environment - Mahendra, Januar Rahadian; Aldyan, Rizal Akbar; Emovwodo, Silas Oghenemaro (CV. Ius et Ambientis, 2024)
The Indonesian government has implemented specific measures that have negatively impacted the environmental sector to enhance economic growth. In response to worldwide pressure and growing internal awareness, the Indonesian government implemented